(untitled) (Comprehensive Journal of Science, 2026)
This paper presents the design and implementation of a low-cost wireless hand-gesture-controlled wheelchair aimed at improving mobility and independence for individuals with physical disabilities. The proposed system uses an MPU6050 inertial measurement unit (IMU) embedded in a wearable glove to detect hand orientation and motion. The sensed data are processed by an Arduino Nano microcontroller and then transmitted wirelessly via an NRF24L01 module to a receiver unit installed on the wheelchair. At the wheelchair side, a second Arduino Nano receives and interprets the transmitted commands, while an L298N motor driver controls two DC motors to perform directional movements, including forward, backward, left, right, and stop. The system architecture is designed with a strong focus on affordability, ease of use, and dependable performance. Experimental testing under indoor conditions showed smooth system operation, stable wireless communication, accurate gesture recognition, and fast motor response. The findings indicate that IMU-based hand-gesture control can provide a practical and accessible alternative to conventional joystick-based wheelchair control, especially for users with limited upper-limb mobility.